UWKS Students' Perception Of The Implementation Of The Core Tax Administration System (CTAS) - Wiwin Wahyuni; Lilik Mardiana; Kharis Marpurdianto (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
To support economic transformation and encourage quality economic growth, the 2024 Draft State Budget (RAPBN) carries the theme "Accelerating Inclusive and Sustainable Economic Transformation." Fiscal reform is necessary, one of which is through optimizing state revenues. In line with efforts to fulfill SDG 8, tax revenue, as the largest source of state revenue, is an appropriate instrument for realizing the intended economic growth. However, when viewed from the level of tax compliance, reflected in the trend of a relatively low tax ratio, Indonesia's tax revenue is considered suboptimal. Responding to this issue, the government continues to strive for digital transformation in the tax sector to be able to reach all taxpayers in Indonesia through a system update called the Core Tax Administration System (CTAS). The Core Tax system is specifically designed to detect taxpayers who are negligent in paying taxes, thus assisting the Directorate General of Taxes (DGT) in imposing fines or outreach to these taxpayers to increase tax compliance. This study aims to determine the perceptions of accounting students regarding the potential and challenges of the Core Tax Administration System (CTAS) in encouraging tax compliance in Indonesia and analyze the challenges of implementing the Core Tax system in the Indonesian tax administration system. This research is a descriptive study with a quantitative approach using a survey method.